2009
DOI: 10.1002/rcm.4192
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation pathways of 2,3‐dimethyl‐2,3‐dinitrobutane cations in the gas phase

Abstract: Abstract2,3‐Dimethyl‐2,3‐dinitrobutane (DMNB) is an explosive taggant added to plastic explosives during manufacture making them more susceptible to vapour‐phase detection systems. In this study, the formation and detection of gas‐phase [M+H]+, [M+Li]+, [M+NH4]+ and [M+Na]+ adducts of DMNB was achieved using electrospray ionisation on a triple quadrupole mass spectrometer. The [M+H]+ ion abundance was found to have a strong dependence on ion source temperature, decreasing markedly at source temperatures above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Associations between M and reactant ions culminate with product ions derived from the sample, e.g., MH + (H 2 O) n , M – (H 2 O) n , and MCl – (H 2 O) n , where n depends upon the temperature and the moisture content of the supporting gas atmosphere. Additionally, fragment ions may form in ion sources when moisture is 1 ppm or below and temperatures are 150 °C or greater. Ionization reactions are confined in a section of the drift tube, the reaction region, which includes the ion source and a volume for mixing of sample neutrals and reactant ions.…”
Section: Introductionmentioning
confidence: 99%
“…Associations between M and reactant ions culminate with product ions derived from the sample, e.g., MH + (H 2 O) n , M – (H 2 O) n , and MCl – (H 2 O) n , where n depends upon the temperature and the moisture content of the supporting gas atmosphere. Additionally, fragment ions may form in ion sources when moisture is 1 ppm or below and temperatures are 150 °C or greater. Ionization reactions are confined in a section of the drift tube, the reaction region, which includes the ion source and a volume for mixing of sample neutrals and reactant ions.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the protonated molecule [DMNBþH] þ is susceptible to dissociation induced by heat or collision. It was also stated that the propensity of DMNB to form stable sodium adducts can be exploited via DESI-MS detection (Paine et al, 2009). Very recently, the presence of oligoperoxides in TATP was analyzed using CI-MS and ESI-MS with CID reactions.…”
Section: Spectrometry For Explosivesmentioning
confidence: 99%
“…While many solid-state explosives exhibit distinct THz spectra, not all do, and therefore, it is possible that the substance may alternatively be detected and identified through the THz absorption of an added taggant molecule. Since the early 1990s, two laws, the Antiterrorism Act of 1996 in the United States and another by the International Civil Aviation Organization in 1991, have been passed that require the addition of detecting taggants to plastic bonded explosives (i.e., PETN and HMX) and, consequently, making it illegal to manufacture, sell, and import these explosives without any detection agent. , Generally, the taggant agent cannot alter the properties of the tagged explosive as well as having a much higher vapor pressure than the explosive itself, which consequently allows for easier detection of the concealed explosive using techniques such as ion-mobility spectrometry. Commonly used taggants include 2-nitrotoluene, 4-nitrotoluene, ethylene glycol dinitrate, and 2,3-dimethyl-2,3-dinitrobutane (DMDNB) .…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used taggants include 2-nitrotoluene, 4-nitrotoluene, ethylene glycol dinitrate, and 2,3-dimethyl-2,3-dinitrobutane (DMDNB) . DMDNB, a volatile organic compound, is the most commonly used taggant in the United States since it has no wide industrial use, has a high vapor pressure (2.07 × 10 –3 Torr at 298 K), and a very low concentration is required for its detection (roughly 0.1% as compared to approximately 0.5% of 2- or 4-dinitrotoluene) . While gas-phase detection of DMDNB is well established, difficulty would be found detecting this taggant within an explosive that is sealed in an airtight container.…”
Section: Introductionmentioning
confidence: 99%